Axially loaded RC columns repaired on one side with cement-based mortars. (20th July 2018) - Ortega, A. Irene; Pellicer, Teresa M.; Calderón, Pedro A.; Adam, Jose M.
Graphical abstract: Highlights: Retrofitting RC structures is now becoming increasingly important. This work studies the effectiveness of one-sided repairs on RC columns. Columns are repaired with R3 and R4 cement-based mortars. 18 RC columns were experimentally tested to failure. Abstract: This paper describes and analyses the results of an experimental programme carried out at the Universitat Politècnica de València on 18 reinforced concrete (RC) columns, 12 of which had been repaired on one side with cement-based mortar before being subjected to axial loading until failure. The objective of the research was to determine the performance of the columns that had been repaired using different mortars, evaluate the influence of Class R3 and R4 mortar used and of the application of a binder or bonding agent. The results obtained were compared with those of the undamaged control columns and those of the unrepaired damaged columns to obtain values for the efficiency of the repairs and for the improvement in the load-bearing capacity of the columns. The results obtained indicate that the columns repaired with Class R3 mortar, with a lower elasticity modulus, function in better way than the Class R4 repaired ones. The presence or absence of a binder was not found to be a determining factor in improving the behaviour of the repaired elements. The chief novelty of the study lies in the fact that it is the first experimental study on RC columns totally repaired on one side only, using different types of mortar with and without the application of a binder.